Idle No More: identité autochtone actuelle, solidarité et justice sociale : Entrevue avec Melissa Mollen Dupuis et Widia Larivière - Gentelet, Karine (Nouvelles pratiques sociales, 2014)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; environnement; féminisme autochtone; militance; pol4105; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; science politique et droit; thématiques

The winter we danced: voices from the past, the future, and the Idle No More movement - Kino-nda-niimi Collective (ARP Books, 2014)
"The Winter We Danced is a vivid collection of writing, poetry, lyrics, art and images from the many diverse voices that make up the past, present, and future of the Idle No More movement. Calling for pathways into healthy, just, equitable and sustainable communities while drawing on a wide-ranging body of narratives, journalism, editorials and creative pieces, this collection consolidates some of the most powerful, creative and insightful moments from the winter we danced and gestures towards next steps in an on-going movement for justice and Indigenous self-determination"
Section: 439 pages : illustrations (certaines en couleur) ; 22 cm
Keywords: 2000 à aujourd'hui; 2010-2019; DIG; amériques; approches et analyses; arts; canada; care; cours; créativité; discipline; féminisme autochtone; images; justice sociale; militance; musique; pol4105; poésie; premier cycle; périodes historiques; régions géographiques; santé; thématiques; études littéraires